Metaphysical themes, 1274-1671 - Pasnau, Robert (Oxford : Oxford University Press, 2011)
Robert Pasnau tells a continuous story about the development of philosophy from the late Middle Ages into the early modern era of the 17th century. The focus is questions in metaphysics concerning the nature of matter and the structure of the material world.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Metaphysics -- History